Study on Motion Management of Pancreatic Cancer Treated by CyberKnife - Jing, Shenghua; Jiang, Changchen; Ji, Xiaoqin; Qiu, Xiangnan; Li, Jing; Sun, Xiangdong; Zhu, Xixu (Frontiers in Oncology, 2021)
Purpose: To investigate the movement characteristics of pancreas and the clinical accuracy of tracking pancreas with SRTS (Synchrony respiratory tracking system, SRTS) during the treatment of CyberKnife. These data provide a clinical data basis for expanding the margins of pancreatic tumor target. Methods and Materials: 42 patients with pancreatic cancer treated by CyberKnife were retrospectively studied. The pancreatic displacement calculated from the X-ray images collected during the time interval between two consecutive bed movements constitute a data set. Results: The total mean motion amplitude and standard deviation of pancreatic tumors in SI, LR, AP and radial directions were 3.66 ± 1.71 mm, 0.97 ± 0.62 mm, 1.52 ± 1.02 mm and 1.36 ± 0.49 mm, respectively. The overall mean correlation errors and standard deviation were 0.82 ± 0.46 mm, 0.47 ± 0.33 mm, 0.41 ± 0.24 mm and 0.98 ± 0.37 mm, respectively. The overall mean prediction errors and standard deviation were 0.57 ± 0.14 mm, 0.62 ± 0.28 mm, 0.39 ± 0.17 mm and 1.58 ± 0.36 mm, respectively. The correlation error and prediction error of pancreatic tumors at different anatomical positions in SI, LR and AP directions were statistically significant (p＜0.05). Conclusions: The tumor motion amplitude, the tumor location and the treatment time are the main factors affecting the tracking accuracy. The pancreatic tumors at different anatomical locations should be treated differently to ensure sufficient dose coverage of the pancreatic target area. Key words: CyberKnife, SRTS，pancreatic cancer，tumor motion management, expansion margin